Faktor-Faktor yang Berhubungan dengan Pernikahan Dini - Maya Febriyanti; Sri Astuti; Ade Julianti (Oksitosin : Jurnal Ilmiah Kebidanan, 2023)
It is estimated that 140 million, or 28 cases per 1,000 women worldwide, early marriage will occur in 2011 and 2022. This research was a quantitative study with a cross-sectional approach and a descriptive design to examine factors related to early marriage in Lasi City, Dompu Regency. in 2021. The population of this study consisted of 48 mothers who were married in 2021. The Chi Square test was used for statistical test analysis in this study. Statistical test results show that information, economics and customs are related to early marriage with each p value (0.00). It is hoped that health workers can really provide education to parents and youth about the best age to marry and have children through health promotion activities